The role of kinematic mental simulation in creating false memories - Ianì, Francesco; Mazzoni, Giuliana; Bucciarelli, Monica (Journal of cognitive psychology (Hove, England), 2018)
Our investigation focuses on memory for scenes depicted in photos. According to the mental model theory, the observation of a static scene depicted in a photo which portrays an actor near to perform an action can trigger a kinematic mental simulation of that action unfolding in time. The deriving prediction is that such a kinematic mental model supports the creation of a false memory of the actor performing an advanced phase of the action. We test this prediction in three experiments in which participants are presented with static scenes of actions, and after three days they perform a recognition task in which they assess recognition of old and novel static scenes depicting actions. The results confirm that false memories occur for actions that represent the unfolding over time of the static action initially observed. Our theoretical framework can accommodate also several previous findings in the literature on false memories.